The Effect of Virtual Reality Game Based Learning to Enhance STEM Literacy in Energy Concepts - Widiyatmoko, A.; Nugrahani, R.; Yanitama, A.; Darmawan, M. S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
STEM literacy is a competency that students must have in the 21st century. The aim of this research is to analyze the effectiveness of Virtual Reality-Game based Learning (VRGBL) to enhance junior high school students' STEM literacy. This research is Quasi Experimental Design. The sample for this research was students at Junior High School Class VIII G (experimental class) and Class VIII H (control class) of SMP Negeri 27 Semarang for academic year 2023/2024 odd semester period. The data analysis of this research was focused on the effect of VRGBL on students' STEM Literacy on energy concept. The result of the study shows that STEM literacy for 8th-grade students consists of four components: science literacy, technology literacy, engineering literacy, and mathematic literacy. The results revealed that there is a significant different between the control and experimental group that is Mexp = 83.59, SDexp = 7.54, Mcon = 65.48, SDcon = 7.89, t = 0.00, sig 0.05. The research results showed that VRGBL is effective in enhancing students' STEM literacy in energy concepts with N-gain in the experimental class of 0.57 in the medium category compared to the control class of 0.28 in the low category.